Coupling of online control and inhibitory systems in children with atypical motor development: A growth curve modelling study - Ruddock, S.; Caeyenberghs, K.; Piek, J.; Sugden, D.; Hyde, C.; Morris, Susan; Rigoli, D.; Steenbergen, B.; Wilson, P. (Academic Press, 2016)
Introduction: Previous research indicates that children with Developmental Coordination Disorder (DCD) show deficits performing online corrections, an issue exacerbated by adding inhibitory constraints; however, cross-sectional data suggests that these deficits may reduce with age. Using a longitudinal design, the aim of the study presented here was to model the coupling that occurs between inhibitory systems and (predictive) online control in typically developing children (TDC) and in those with Developmental Coordination Disorder (DCD) over an extended period of time, using a framework of interactive specialization. We predicted that TDC would show a non-linear growth pattern, consistent with re-organisation in the coupling during the middle childhood period, while DCD would display a developmental lag. Method: A group of 196 children (111 girls and 85 boys) aged between 6 and 12 years participated in the study. Children were classified as DCD according to research criteria. Using a cohort sequential design, both TDC and DCD groups were divided into age cohorts. Predictive (online) control was defined operationally by performance on a Double-Jump Reaching Task (DJRT), which was assessed at 6-month intervals over two years (5 time points in total). Inhibitory control was examined using an anti-jump condition of the DJRT paradigm whereby children were instructed to touch a target location in the hemispace opposite a cued location.Results: For the TDC group, model comparison using growth curve analysis revealed that a quadratic trend was the most appropriate fit with evidence of rapid improvement in anti-reach performance up until middle childhood (around 8–9 years of age), followed by a more gradual rate of improvement into late childhood and early adolescence. This pattern was evident on both chronometric and kinematic measures. In contrast, for children with DCD, a linear function provided the best to fit on the key metrics, with a slower rate of improvement than controls. Conclusion: We conclude that children with DCD require a more extended period of development to effectively couple online motor control and executive systems when completing anti-reach movements, whereas TDC show rapid improvement in early and middle childhood. These group differences in growth curves are likely to reflect a maturational lag in the development of motor-cognitive networks in children with DCD.